Danger Lies Everywhere and Waits for Us.” Cape Town Metro EMS Ambulance Personnel's Experiences of Risk, Danger and Fear - Beukes, Minette (Department of Public Law, 2023)
Introduction: Emergency medical services (EMS) ambulance personnel have increasingly become victims of violence while providing lifesaving medical services. This is not only a problem experienced globally, but in South Africa as well – particularly by the Metro (public) EMS ambulance personnel in Cape Town. This phenomenon has not yet been formally investigated in South Africa; thus, this study aims address this gap by exploring Cape Town Metro EMS ambulance personnel's experiences of risk, danger and fear associated with crime while performing service calls, and how these experiences shape the delivery of prehospital services. Methods: This study utilised a qualitative research approach to explore Cape Town Metro EMS ambulance personnel's experiences of risk, danger and fear associated with crime while performing service calls. Semi-structured interviews were conducted with a sample of twelve permanently employed and qualified Metro EMS ambulance workers in the city. The study used thematic analysis to identify six main themes within the data set, including: experiences of risk; experiences of danger; experiences of fear; education, training and experience; occupational challenges; and safety interventions and recommendations. Results: This study determined that most Metro EMS ambulance personnel that experience risk on the job, and that they do not feel that their training adequately prepares them for the realities of their occupation, especially in terms of crime. In terms of the experience of danger, respondents noted that certain ambulance divisions work in particularly dangerous areas or ‘red zones', and that these red zones impact negatively on EMS protocol and subsequent service delivery. The most common dangers they experienced included: shootings and getting caught in crossfire; hijackings or attempted hijackings; stoning; robbery or attempted robbery; and being held at gun and knifepoint. Additionally, most respondents felt that the night shift is more dangerous, and that rural areas – and the infrastructural challenges they pose – are seen a danger. Metro EMS ambulance personnel reported that they experienced verbal, physical and sexual abuse from different types of offenders. How Metro EMS ambulance personnel experienced fear differed: 8 participants stated that they get scared while on duty; 2 stated that they do not experience fear; and 2 had mixed feelings about being scared. Some participants indicated that fear does not influence their ability to perform their medical duties optimally, while others were of the opinion that it does, especially in cases where they have been previously victimised. This study also found that participants experienced occupational challenges in terms of their mental health. Participants were generally of the opinion that traumatic calls and victimisation had negative effects on their mental wellbeing, and stated that the counselling services provided to them did not aid in their recovery. The results of this study show that EMS personnel did not feel that the presence of police escorts reduces their experiences or risk, danger and fear. Respondents thus made safety recommendations based on their experiences of risk, danger and fear. Conclusion: The narratives provided by respondents gave an exhaustive overview of their experiences of risk, danger and fear associated with crime – this included whether or not they experience these elements while performing service calls prehospital environment, as well as how they experience it. The majority of Metro EMS ambulance personnel experienced risk, danger and fear associated with crime while performing service calls, and most of the participants believed that these experiences negatively influence service delivery.